Settlement Analysis due to Micro-Tunnelling Works - Che Hassan, Nur Muhammad Hadri (Universiti Teknologi PETRONAS, 2017)
Underground sewage system has been designed with a view to modern man’s inclination toward health, hygiene and his aversion to filth and pollutants. Currently there is on-going project at Ipoh, Perak. It is a project to build a sewerage treatment plant and sub-catchment pipeline network across Ipoh City. Underground pipe usually installed using open-trench method but in this project, the pipe was laid down using trenchless method. Trenchless method involved the use of micro-tunnelling technique. This disquisition is intended to analyse the longitudinal settlement and transverse settlement induced by the micro-tunnelling activity of the 1050mm and 1500mm diameter sewage pipeline at Jalan President Kennedy, Pasir Puteh and Jalan Sri Kinta 1 Ipoh, Perak. A ground level movement were monitor closely using marker placed at the activity location.